Kurikulum Akhlak Neuro-Islamik di Era Post-Truth: Pendekatan Neurosains dan Nilai Tarbiyah - Muhammad Andreansyah Hidayatulloh; Muhammad Zaki Maulana (Educational Research Center, 2025)
The post-truth era and information overload have created an epistemological crisis in education, particularly in shaping the moral character of Muslim youth. The abundance of unfiltered information blurs the line between truth and opinion, thereby challenging the effectiveness of conventional Islamic moral curricula. This article proposes a new formulation in the form of a digital moral curriculum based on neuro-Islamic principles, integrating neuroscience, Islamic epistemology, and tarbiyah values within a transdisciplinary framework. This research employs a critical library research method to formulate the philosophical and pedagogical foundations of an Islamic moral curriculum that is adaptive to the digital context. The findings indicate that a brain-based Islamic ethics learning approach, combined with tarbiyah principles such as sincerity (ikhlas), trustworthiness (amanah), and responsibility, can shape a curriculum structure that is responsive to ethical challenges in the digital age. The implications of this curriculum are expected to provide a more contextual, humanistic, and scientifically grounded design for Islamic moral education.